2003
DOI: 10.1210/jc.2002-021604
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat Mass and Macronutrient Intake in Relation to Circulating Soluble Leptin Receptor, Free Leptin Index, Adiponectin, and Resistin Concentrations in Healthy Humans

Abstract: The adipocyte-derived hormones leptin [which circulates in a free form and bound to a soluble leptin receptor (sOB-R)], adiponectin, and resistin play a key role in regulating energy homeostasis and metabolism. We assessed the association between body composition, total energy, and macronutrient intake and serum leptin, sOB-R, free leptin index, adiponectin, and resistin concentrations in 61 female and 53 male consecutively enrolled healthy Greek students. In this cross-sectional study, total energy and macron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
260
10
18

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(325 citation statements)
references
References 46 publications
37
260
10
18
Order By: Relevance
“…Total energy intake and macronutrient composition of the diet were reported to be associated with sOB-R concentrations. 29 On the other hand, the changes of sOB-R and leptin levels were significantly correlated to the changes in weight status and percentage body fat, pointing to a link between fat mass and leptin and sOB-R levels. It has been suggested that the adipose tissue hormone leptin downregulates the secretion of its own binding protein 15,18 based on the findings that (1) leptin administration suppresses sOB-R levels in adults, 8 (2) a downregulation of leptin receptor isoforms by leptin has been demonstrated in vitro, 30,31 and (3) leptin receptor mutations are associated with high sOB-R levels.…”
Section: Discussionmentioning
confidence: 89%
“…Total energy intake and macronutrient composition of the diet were reported to be associated with sOB-R concentrations. 29 On the other hand, the changes of sOB-R and leptin levels were significantly correlated to the changes in weight status and percentage body fat, pointing to a link between fat mass and leptin and sOB-R levels. It has been suggested that the adipose tissue hormone leptin downregulates the secretion of its own binding protein 15,18 based on the findings that (1) leptin administration suppresses sOB-R levels in adults, 8 (2) a downregulation of leptin receptor isoforms by leptin has been demonstrated in vitro, 30,31 and (3) leptin receptor mutations are associated with high sOB-R levels.…”
Section: Discussionmentioning
confidence: 89%
“…The higher serum resistin levels of girls compared to boys are in concordance with most studies in adults. 6,13,16 Besides sexual dimorphism of body fat distribution differences in the sex steroids are discussed to be responsible for the observed differences. 12,15,27,28 However, resistin concentrations have been reported to be independent of menstruation cycle and sex hormones in adult women 7 and resistin levels did not significantly differ between prepubertal and pubertal boys.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Studies in humans are even more controversial. 4,5 In crosssectional studies in adulthood, serum resistin was reported to be related to fat mass [6][7][8] and to insulin resistance, [9][10][11][12] while other reports reveal no correlations to BMI, percent body fat 11,[13][14][15] or to insulin sensitivity. 13,14,16,17 Longitudinal data are necessary to analyze the relationships between resistin, obesity, and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Intraassay CsV was 3.4% and interassay CsV was 6.9%. 18 Retinol binding protein-4 was measured using a RBP-4 (Human) enzyme immunoassay (EIA) kit (Phoenix Pharmaceuticals, Inc., Burlingame, CA, USA). The intra-and interassay CsV were less than 5.0% and less than 14.0%, respectively.…”
Section: Assessmentsmentioning
confidence: 99%